Relationship between managers' training assignments and trainees 'perceived value in a defence based higher education institution - Azman Ismail; Muhammad Zulfadhlizam Ghazali; Mohammed Zain Yusof (Pusat Perkembangan Pelajar ,U.K.M, 2013)

(untitled)
The primary objective of this study is to investigate the relationship between managers' training assignments (i.e., mandatory and voluntary) and trainees 'perceived value. A survey method was employed to gather 142 usable questionnaires from a group of military officers, namely military cadet officers in a defence based higher education institution, Malaysia. The outcomes of SmartPLS path model showed two important findings: first, relationship between mandatory significantly correlated with trainees 'perceived value. Second, relationship between voluntary significantly correlated with trainees 'perceived value. This result confirms that the ability of managers to properly implement mandatory and voluntary assignments in encouraging employees to attend and learn in training programs has been an important predictor of trainees 'perceived value in the organizational sample. Further, this study provides discussion, implications and conclusion.